Innovative and sustainable approaches to seasonal visitor attraction development – case study: Posavina corn maze ‘Hrvatica’ - Gasparović, Ana; Matkerić, Katarina (Crisis Management Days, 2024)
Posavina corn maze ‘Hrvatica’ was developed in Lijevi Dubrovčak in the rural area of Ivanić-Grad in 2022 and 2023 to valorize and promote local heritage in an innovative manner. The project was initiated by the local Tourist board and developed in cooperation with the Friends of Heritage association and the local folklore society KUD Posavec. Lijevi Dubrovčak developed rich traditions and customs which can also be seen in folk costumes, one of which has been recognized nationally - Hrvatica. By using the costume embroidery as a conceptual design inspiration and sealing it into the landscape significant for the local area, the project emphasized and represented the local community, heritage, environment and character of the space. Additional value was given by interlacing the maze with informative panels and an interactive ethnological game, which was installed in the maze for self-guided tours. The goal was to encourage visitors to get to know the cultural and historical heritage of the settlement. Participation was free and available to everyone by scanning QR codes. Development of two versions (for children and for adults) contributed to the inclusiveness. The use of digital tools helped to attract youth, and to analyse visits to the maze. For example, a higher attendance was observed during Ivanić-Grad events and afternoon hours. A new, seasonal event "Posavina Days" was also organised, during which the locals showcased their local crafts, cuisine and folklore dance. Additionally, visitors could experience traveling to the maze with a carriage that was carried by specific Posavina horses, with the aim to emphasize another heritage element - horse breed developed in this area for centuries. The attraction lasted from summer to autumn and it changed as the season changed in terms of colour and growth. This is an excellent learning platform for children and youth to experience changes in nature. Project emphasized the importance of smaller local areas and dispersion of tourist attraction in the broader areas, away from already known urban places. It helped to inspire and remind the local community of the natural and cultural values they have and which they can use as a tool to develop the area in innovative ways. The maze also promoted physical and cognitive well-being, spending time in the open air and in the natural surroundings, moving and using your skills to participate in educational and playful activities. We believe that such a project is a great example of sustainable tourism and heritage interpretation which involves local community and regains a sense of belonging. Posavina corn maze was highly recognized by a broad range of national media which helped to promote the cultural and natural heritage of a small rural settlement of Dubrovčak Lijevi to a wide national public.